Antimicrobial Peptides and Nanotechnology, Recent Advances and Challenges - Biswaro, Lubhandwa S.; da Costa Sousa, Mauricio G.; Rezende, Taia M. B.; Dias, Simoni C.; Franco, Octavio L. (Frontiers in Microbiology, 2018)
Antimicrobial peptides are sequences of amino acids, which present activity against microorganisms. These peptides were discovered over 70 years ago, and are abundant in nature from soil bacteria, insects, amphibians to mammals and plants. They vary in amino acids number, the distance between amino acids within individual peptide structure, net charge, solubility and other physical-chemical properties as well as differ in mechanism of action. These peptides may provide an alternative treatment to conventional antibiotics, which encounter resistance such as the peptide nisin applied in treating methicillin-resistant Staphylococcus aureus (MRSA) or may behave synergistically with known antibiotics against parasites for instance, nisin Z when used in synergy with ampicillin reported better activity against Pseudomonas fluorens than when the antibiotic was alone. Antimicrobial peptides are known to be active against viruses, bacteria, fungi and protozoans. Nanotechnology is an arena which explores the synthesis, characterization and application of an array of delivery systems at a one billionth of meter scale. Such systems are implemented to deliver drugs, proteins, vaccines, and peptides. The role of nanotechnology in delivering antimicrobial peptides is still at its early development stage. There are challenges of incorporating antimicrobial peptides into drug delivery system. This review intends to explore in depth, the role of nanotechnology in delivering antimicrobial peptides as well as presenting the current advances and accompanying challenges of the technology.